Rapid exclusion of acute myocardial infarction in patients with undetectable troponin using a sensitive troponin I assay. (September 2015) - Body, Richard; Burrows, Gillian; Carley, Simon; Lewis, Philip S
Objective: With a high-sensitivity troponin assay, it may be possible to exclude acute myocardial infarction with a single blood test on arrival in the emergency department by using a novel 'rule out' cut-off set at the limit of detection of the assay. We aimed to determine whether this can also be achieved using a contemporary sensitive troponin assay that does not meet 'high-sensitivity' criteria. Methods: In a prospective diagnostic cohort study, we included patients presenting to the emergency department with suspected cardiac chest pain. For this secondary analysis, serum samples drawn on arrival were tested using a contemporary sensitive troponin I assay (s-cTnI; Siemens Ultra ADVIA Centaur, 99th percentile 40 ng/L, limit of detection 6 ng/L). Acute myocardial infarction was adjudicated by two independent investigators based on reference standard troponin testing ≥12 h after symptom onset. Results: Of 414 participants, 70 (16.9%) had acute myocardial infarction and 205 (49.5%) had initial s-cTnI concentrations below the limit of detection. Using the limit of detection as a 'rule out' cut-off gave a sensitivity of 94.3% (95% CI 86.0–98.4%) for acute myocardial infarction. If only patients with s-cTnI below the limit of detection and no electrocardiogram ischaemia were considered to have acute myocardial infarction 'ruled out' (41.8% of the cohort, n  = 174), sensitivity would rise to 97.1% (90.1–99.7%) and negative predictive value to 98.8% (95.9–99.9%). Conclusions: Acute myocardial infarction cannot be excluded in patients with s-cTnI concentrations below the limit of detection using the contemporary sensitive assay evaluated. Future work with this assay should focus on serial sampling over 1–3 h and combination with clinical information and/or additional biomarkers.